A flexibilização do sigilo bancário e a efetividade dos sistema público de escrituração digital - Sped. - Silva, Leonardo Lins e (2017)
The Public Digital Bookkeeping System - SPED is the new tool available to companies to fulfill their ancillary obligations, all in an exclusively digital environment. This is the new paradigm of ancillary obligations, a sign of the abandonment of physical media by the adoption of digital media, a corollary of the necessary adaptation to technological innovations, to the web world. With the implementation of the SPED project and then of its various modules, it was established the duty to fulfill the business requirements strictly by the digital route. SPED, therefore, represents the most modern in the field of business bookkeeping, consisting of an important instrument in the fight against tax evasion, cost reduction, simplification of ancillary obligations, among other benefits. It is essential, therefore, the study of SPED as the central theme and in the perspective of this, the Instrumental Duties or Accessory Tax Obligations, Digital Certificates and the Brazilian Public Key Infrastructure (ICP-Brasil), and Flexibilization of Banking Secrecy in Brazil. With regard to the methodology applied in the research can be classified as being of the qualitative, applied and explanatory type, being the methods used the bibliographic, the documentary and the case study. The latter consisting of the analysis of the entire content of judgment, votes and shorthand notes of the joint judgment of the Direct Unconstitutionality Actions of No. 2,390; 2.386; 2,397; And Extraordinary Appeal No. 601,314 - São Paulo, with general acknowledged repercussion, where the constitutionality of Articles 5 and 6 of Complementary Law 105/2001 and respective Decrees of No. 4489/2002 and 3724/2001 were declared. The judgment can be classified as being the leading in case of bank secrecy in Brazil and its study arose from the need to analyze the impacts of this decision in SPED. Thus, the result was that access to taxpayers' financial information, regardless of judicial authorization, is not only a measure aligned with the international commitments assumed by Brazil, it is essential to ensure greater effectiveness in the inspection And collection of taxes, reduce costs and time with compliance with ancillary obligations, inhibit the practice of crime of tax evasion, money laundering, evasion of foreign exchange and criminal organization, as well as affirm the effectiveness of SPED in Brazil.